Coaching, 3M behavior change strategy for the prevention of covid-19 transmission in Kupang City, NTT Province, Indonesia - Karolus Ngambut; Michael John S. Takesan (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The spread of Covid19 is not only limited to China; South Korea has confirmed its first case. On January 30, 2020, the World Health Organization announced that Covid19 had become a global pandemic. The Indonesian government has declared Covid19 a non-natural national disaster. To prevent the transmission of Covid19, this is done through the implementation of the 3M Covid19 prevention protocol. For 3M's behaviour to become a community culture, a strategy is needed to disseminate this information, one of which is through coaching carried out in stages. The results of the coaching activity showed that the behaviour of using masks increased by 30.05%, the behaviour of CTPS increased by 30.2%, and the behaviour of guarding distance increased by 30.09%, and the ownership of CTPS facilities at home was 70.65% after coaching. It is suggested that the coaching method can be used more widely to promote 3M behaviour in the community to prevent Covid transmission19